PENGARUH PENDEKATAN OPEN-ENDED DENGAN PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP KEMAMPUAN KONEKSI MATEMATIS SISWA DI SMPIT BINA SALAM BEKASI - Ani, Nurimani; Adinda, Adinda Yasmina Ramadanti (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2023)
This study aims to determine the effect of an open-ended approach with cooperative learning type Student Team Achievement Division (STAD) on students' mathematical connection abilities. The research was conducted at SMPIT Bina Salam, Bekasi City in the framework of the independent learning program in the form of teaching assistance learning activities in educational units. This research method is an experiment. The number of students as many as 54 students in this study. The results showed that there was no difference in the mathematical connection abilities of students who used an open-ended approach with STAD type cooperative learning and expository learning. Keywords: Open-Ended Approach, STAD type Cooperative, Mathematical Connection capabilities.